Pengembangan Rancang Bangun Game Edukasi Logistik "Stowagame" Mengenai Penataan Kontainer Di Bay Kapal - Hendriyono Rachman; Ahmad Rusdiansyah (Jurnal Teknik Industri, 2012)
Development of educational games focuss on the problem occured on bay management, primarily on loading container at ship bay. The loading plan problem in ship bay commonly known as Master Bay Plan Problem (MBPP). The complexity of MBPP can be seen on its constraints, that are container weight, container destination, container size, container type, and the arrangement rule of container. The study case and playing rules in this game development are adjusted to contextual theory and real situation occured in container arrangement at ship bay. The prototype of this game is called StowaGame. StowaGame is a simulation-based educational games related to container arrangement in ship bay. This software are built with the integration of MBPP and entertainment concept. The effectivity of this educational game will be tested by several player. The MBPP concept of each player will be tested before and after playing the game. Paired-t test calculation shows that p-value is less than 0,05. Thus, it can be concluded that the educational game can educate people with container arrangement concept in ship bay.